The Gospel "according to Homer and Virgil " cento and canon - Sandnes, Karl Olav, 1954- (Novum Testamentum, Supplements, 2011)
In the fourth century C.E. some Christians paraphrased the stories about Jesus' life in the style of classical epics. Imitating the genre of centos, they stitched together lines taken either from Homer (Greek) or Virgil (Latin). They thus created new texts out of the classical epics, while they still remained fully within the confines of their style and vocabulary. It is the aim of this study to put these attempts into a historical and rhetorical context. Why did some Christians rewrite the Gospel stories in this way, and what came out of this? On the basis of these Christian centos, it is natural to address the view held by some scholars, namely that New Testaments narratives are imitations of the epics.